TANGGUNG JAWAB ORANG TUA DALAM MENDIDIK ANAK USIA DINI MENURUT Al-QUR’AN - Enok Hilmatus Sa’adah; Soni Samsu Rizal (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Tarbiyah, Institut Agama Islam Darussalam (IAID) Ciamis Jawa Barat, 2019)
This study aims to determine the contents of Al-Qur'an Surah An-Nisa verse 9 in the book Tafsir Al-Maraghi, as well as to determine the relevance of parental responsibilities in educating young children according to Al-Qur'an Surah An-Nisa verse 9. The results of the study show: The An-Nisa verse verse 9 gives instructions to parents, so they have to worry if they later leave a weak and helpless descendant; the responsibility of parents in educating early childhood according to Al-Qur'an An-Nisa verse verse 9 which includes physical and spiritual education, aqeedah education, moral education. The relevance of parental responsibilities in educating young children is that parents should feel worried if their offspring are in a weak condition so that each parent is required to form a quality generation with physical and spiritual education, including encouraging children to exercise and play. Parents are encouraged to apply Aqidah education to children one of them by introducing the understanding that God created all creatures.